Pemikiran K.H. Hasyim Asy’ari Tentang Karakter Religius Anak Usia Sekolah Dasar - Ririn Riswana Mandar (Peneliti.net, 2023)
Based on current developments in science and technology, there are deviant behaviors that are always encountered in everyday life. This happened not because of the educational path taken. However, one of them is in strengthening religious character from an early age. So how important is the religious character instilled in students, especially elementary school age children. In addition, KH Hasyim Asy'ari is one of the figures who is active and has great concern in the world of Islamic education. And in the implementation of education more emphasis on character building. The research method used in this research is library research method. The type of research used is intellectual biography. This is done to find out the life of Hasyim Asy'ari in his relationship with the community and to find out the extent of his thoughts and contributions to the development of the religious character of elementary school-age children. The results of this study indicate that KH Hasyim Asy'ari's thoughts about the religious character that elementary school-age children must have, namely purifying the heart, improving intentions, behaving qana'ah, being wara', and behaving patiently. And in efforts to instill religious character values, strategies and methods are needed to support the implementation of character education for elementary school children, namely exemplary, teaching students with love and compassion, motivating students, stopping bad behavior by students, being weak gentle and humble.